A surgical strategy to prevent delayed epidural hematoma after posterior fossa surgery using lateral suboccipital retrosigmoid approach. (June 2018) - Lee, Seunghoon; Park, Sang-Ku; Joo, Byung-Euk; Lee, Jeong-A; Kong, Doo-Sik; Park, Kwan
Highlights: Postoperative delayed epidural hematoma (EDH) after posterior fossa surgery is rare. Delayed EDH results in a catastrophic clinical manifestation. Key dural tacking sutures prevent delayed EDH effectively. Abstract: Although non-traumatic postoperative delayed epidural hematoma (EDH) after posterior fossa surgery is rare, measures to prevent it need to be pursued due to its catastrophic results. In this report, we describe a surgical strategy to prevent delayed EDH after posterior fossa surgery. Key dural tacking sutures were performed at the medial and cephalic margin of the dura. We have performed key dural tacking sutures on 454 patients with neurovascular compression syndrome during microvascular decompression surgeries since April 2016, and no hemorrhagic complication, including delayed EDH, occurred. We discovered that key dural tacking sutures can be helpful in preventing postoperative posterior fossa delayed EDH.